Tramadol-induced hiccups: a case-noncase study in the European pharmacovigilance database - Montserrat García; Unax Lertxundi; Carmelo Aguirre (SAGE Publishing, 2021)
Background: Hiccups are usually benign and self-limiting, but can sometimes be persistent. If left untreated, they can provoke severe discomfort, and even death. Hiccups can be idiopathic, organic, psychogenic, and caused by drugs. Although some case reports have suggested a possible association between tramadol and hiccups, to our knowledge, no study has analyzed this possible relationship. The aim of this study was to analyze whether a disproportionate number of cases of hiccups are reported for tramadol in the EudraVigilance database. Methods: A case-noncase study was conducted to assess the association between hiccups and tramadol, calculating reporting odds ratios (RORs) from 1 January 1995 to 11 September 2020. Cases were selected using the preferred term 'Hiccups'. The noncases used as controls were all other adverse drug reaction reports recorded in EudraVigilance during the same period. Exposure was defined as exposure to tramadol among cases and noncases. To reduce the risk of confounding by indication, the RORs for tramadol compared with other opioids were obtained. Additionally, we performed a confirmatory analysis in the World Health Organization pharmacovigilance database, VigiBase ® . Results: There were 3089 cases of hiccups in the 7,213,623 reports. Tramadol was involved in 50 cases. The ROR for tramadol exposure was 3.35 [95% confidence interval (CI) 2.53-4.43]. This association persisted when comparing tramadol with other opioids; ROR: 2.13 (95% CI 1.52-2.99). Disproportionality was also observed in VigiBase ® : ROR 1.69 (95% CI 1.47-1.93). Conclusion: Our study confirms, for the first time, a possible signal for a tramadol-hiccups association. Nevertheless, observational analytical studies are needed to confirm these results Plain Language Summary Evaluation of the relationship between the tramadol and the risk of hiccups Introduction: Hiccups are sudden involuntary contractions of the diaphragm. This involuntary contraction causes the vocal cords to close very briefly, which produces the characteristic sound of a hiccup. Hiccups are usually benign and self-limiting, but can sometimes be persistent. If left untreated, they can provoke severe discomfort, depression, disability, and in the most extreme cases, even death. Drugs are a rare cause of hiccups. Methods: This study investigated the possible association between tramadol and hiccups (an unmentioned adverse drug reaction in the Summary of Product Characteristics) in the European pharmacovigilance database (EudraVigilance) and a confirming analysis in the World Health Organization pharmacovigilance database (VigiBase). Results: Our analysis shows that hiccups is relatively more frequently reported in association with tramadol than with other medicinal products, with EudraVigilance and VigiBase confirming this association. Conclusion: Tramadol is an opioid analgesic indicated, alone or in combination with dexketoprofen or paracetamol for pain with various causes, so healthcare professionals and patients should be aware of this possible association.